2021
DOI: 10.1088/1742-6596/1990/1/012072
|View full text |Cite
|
Sign up to set email alerts
|

3D printing technological modes influence on the performance properties of vehicles plastic parts restored with additive technologies

Abstract: The 3D printing parameters influence on the plastic parts performance properties (water absorption, chemical resistance) created with additive technologies is considered. It has been found that, the filling percentage has the greatest influence on the change in the water absorption value among the other printing parameters. It has been shown that the printed product structure formation should be carried out at a print job creating stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Also, based on the literature review and previous studies, six following parameters that have the greatest impact on the quality of printed master models have been identified [13,17]:…”
Section: Methodology and Results Of Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, based on the literature review and previous studies, six following parameters that have the greatest impact on the quality of printed master models have been identified [13,17]:…”
Section: Methodology and Results Of Experimental Studiesmentioning
confidence: 99%
“…Based on the literature review and previous studies, FDM technology has been identified as the most suitable for use in conjunction with casting because of the ease of producing master models for casting methods such as investment casting and burn-out casting, the models produced have high strength and surface purity [14][15][16][17][18].…”
Section: Fusedmentioning
confidence: 99%